60 Years of Combining Tranylcypromine: A Systematic Review of Available Evidence. Issue 1 (January 2022) - Wagner, Elias; Seemüller, Florian; Hasan, Alkomiet
Abstract: Background: Tranylcypromine is the only irreversible monoamine oxidase inhibitor that is approved in the United States and in Europe for the management of treatment-resistant major depressive disorder. Comprehensive data in the literature regarding the efficacy and tolerability of tranylcypromine (TCP) combination strategies have not been systematically investigated yet. Methods: We conducted a systematic review of available literature based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Study types considered eligible for inclusion were studies that reported information on efficacy and/or tolerability/adverse effects of pharmacological TCP add-on or coadministration strategies among people with psychiatric disorders. Results: Ninety-six articles were included in qualitative analyses. A relevant body of evidence shows that TCP combined with first- and second-generation antipsychotics seems relatively safe and might have beneficial effects in some patients with depressive disorders, although caution is needed with some second-generation antipsychotics that have proserotonergic activity. Although evidence is not entirely consistent, amitriptyline as add-on agent might be efficacious and associated with a low rate of severe adverse events. Although available data from case reports are scarce, certain other agents, such as trazodone, but also lithium, seem to have a good risk-benefit profile with regard to TCP that should be further investigated in the context of high-quality studies. Conclusions: Any combination of a psychotropic with TCP should be preceded by an evaluation of drug-to-drug interaction and an informed consent process and followed by close monitoring. Before any combination strategy, doctors should reevaluate factors of pseudo–treatment resistance, such as rapid-metabolizing status, noncompliance, trauma, alternative diagnosis, or drug abuse.